ANALYSIS OF MARKET DYNAMICS AND CONSUMPTION TRENDS OF PALM SUGAR COFFEE IN WEST JAVA - Gustina Hidayat; Aa Kartiwa; Syifa Deliasari; Lusiana Sihombing (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The increasing popularity of palm sugar coffee reflects a growing consumer preference for healthier and locally sourced beverage products in Indonesia. This study aims to analyze the market dynamics and consumption trends of palm sugar coffee in West Java and to identify the key factors influencing consumer purchase decisions. A quantitative explanatory approach was employed using a survey of 182 palm sugar coffee consumers in several cities and regencies in West Java. Data were analyzed using descriptive statistics and Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique. The results indicate that the palm sugar coffee market is characterized by high price volatility, intense competition, and wide product accessibility, while product differentiation remains at a moderate level. Consumption trend analysis reveals that palm sugar coffee is consumed frequently and is primarily motivated by health awareness and preference for local products. The SEM-PLS findings show that health awareness, lifestyle orientation, and product differentiation have significant positive effects on purchase decisions, whereas market dynamics do not exert a significant direct influence. This study contributes to the literature by demonstrating that intrinsic consumer factors are more decisive than external market conditions in shaping purchasing behavior in the emerging palm sugar coffee market. The findings provide strategic insights for MSME producers and policymakers to enhance product innovation, health-oriented branding, and lifestyle-based marketing in order to strengthen the competitiveness and sustainability of palm sugar coffee in West Java.